This meat or that alternative? How masculinity stress influences food choice when goals are conflicted - Leary, R. Bret; MacDonnell Mesler, Rhiannon; Montford, William J.; Chernishenko, Jennifer (Frontiers in Nutrition, 2023)
This research integrates literature on masculinity stress – the distress experienced as the result of a perceived discrepancy with male gender norms – with research on goal conflict to examine preferences for plant-based meat alternatives (PBMAs). Men experiencing masculinity stress are likely to hold salient a goal of being masculine, which should lead to less preference for PBMAs. However, many of these men simultaneously hold competing goals, such as making ethical food choices, which remain inhibited in favor of the focal masculinity goal. We argue that once men experiencing masculinity stress highlight their masculinity through the selection of a manly product, they satisfy that higher-order goal and are then free to pursue previously inhibited goals, such as making an ethical choice through the selection of PBMAs. We present the results of three studies supporting these expectations. Study 1 tests the link between masculinity stress and meat (alternative) consumption using consumer search behavior collected from Google Trends, showing that masculinity stress is positively (negatively) correlated with searches for red meat (PBMAs). Study 2 shows that men experiencing masculinity stress are more inclined to choose PBMAs, provided they are presented within a masculine product context. Study 3 presents a parallel mediation model, showing that ethical considerations (as opposed to masculine goals) shape the choice of PBMA preference. We conclude with a discussion of theoretical implications for the impression management strategies utilized by men experiencing masculinity stress and practical implications for the growing PBMA industry.